A narancsligettől a harisnyagyárig: Felvetések a Mágia kritikai kiadásához - Győrei, Zsolt (Studia Litteraria, 2018)
Mágia, one of Dezső Kosztolányi’s lyrical works, was first published in 1912 by tevan Printing-House. With a few minor changes the book was published again in 1920, and finally in 1935 as a part of the Collected Poems, in which the poet chose to feature only 19 of his poems instead of the original 46. The study focuses on the complete 46-poem-long version, and offers an insight of the creation, composition and reception of the volume. The aim of these aspects are to explain the editorial decision behind the soon-to-be-released critical edition, which is questioning the validity of the abridged edition: the ultima manus principle cannot be validated because of the last edition’s abbreviated nature. The study argues that the second edition should have a privileged position over the last edition of 1935.